Community shift of ammonia-oxidizing bacteria along an anthropogenic pollution gradient from the Pearl River Delta to the South China Sea - Cao, Huiluo (Springer-Verlag, 2011)
The phylogenetic diversity and abundance of ammonia-oxidizing beta-proteobacteria (beta-AOB) was analyzed along an anthropogenic pollution gradient from the coastal Pearl River Delta to the South China Sea using the ammonia monooxygenase subunit A (amoA) gene. Along the gradient from coastal to the open ocean, the phylogenetic diversity of the dominant genus changed from Nitrosomonas to Nitrosospira, indicating the niche specificity by these two genera as both salinity and anthropogenic influence were major factors involved. The diversity of bacterial amoA gene was also variable along the gradient, with the highest in the deep-sea sediments, followed by the marshes sediments and the lowest in the coastal areas. Within the Nitrosomonas-related clade, four distinct lineages were identified including a putative new one (A5-16) from the different sites over the large geographical area. In the Nitrosospira-related clade, the habitat-specific lineages to the deep-sea and coastal sediments were identified. This study also provides strong support that Nitrosomonas genus, especially Nitrosomonas oligotropha lineage (6a) could be a potential bio-indicator species for pollution or freshwater/wastewater input into coastal environments. A suite of statistical analyses used showed that water depth and temperature were major factors shaping the community structure of beta-AOB in this study area. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00253-011-3636-1) contains supplementary material, which is available to authorized users.